All-solid-state chloride sensor for in-situ monitoring of chloride penetration in concrete. (28th November 2022) - Du, Zhenxing; Tian, Li; Wang, Penggang; Chen, Zhaoyi; Cui, Dongbo; Jin, Zuquan; Zhang, Hai
Highlights: An all-solid-state chloride sensor constituted with Ag/AgCl working electrode and Mn/MnO2 reference electrode was developed. The chloride sensor shows good stability, ideal chloride response, and strong resistance to ionic interference. The chloride sensor can accurately monitor the chloride content changes of the mortar specimens during the chloride penetration process. Abstract: In this study, an all-solid-state chloride sensor constituted with Ag/AgCl working electrode and Mn/MnO2 reference electrode was developed. The Ag/AgCl electrode fabricated with galvanostatic anodization method and Mn/MnO2 fabricated with powder compaction method exhibited homogeneous micro-structures. The as-prepared chloride sensor showed good ability of polarization resistance, long-term stability, perfect Nernst response, and low hysteresis effect in solutions. The influence of pH, temperature, and interfering ions on the chloride response of the sensor was also systematically investigated. Furthermore, the chloride sensor was embedded in the mortar specimen and used to monitor the chloride penetration process during the capillary absorption test. The results indicate that the chloride sensor can provide accurate chloride content variations of the mortar specimens, and it has great potential for non-destructively monitoring the chloride penetration in concrete structures.